AUTOSPY STUDY TO DETERMINE FETAL ANOMALY: A RETROSPECTIVE COHORT STUDY - R M POTEKAR,; JAVALGI P ANITA,; B R YELIKAR, (International Journal of Pharma and Bio Sciences, 2014)
Congenital anomalies have become an important cause of perinatal mortality and morbidity in both developing and developed countries. Present study was done to know the frequencies of congenital anomalies, its association with maternal diseases, maternal age and co-relation with ultrasonographic findings.Total 54 autopsy cases were studied in 6 year span from January 2007- December 2012.Consent for autopsy was obtained from either of the parent after explaining the need. Each foetus was examined according to predetermined protocol which included ultrasound diagnosis, photograph, whole body X ray (when required), external and internal examination.Out of 54 fetal autopsies, 35(64.8%) cases had congenital anomaly, 10cases (18.5%) had shown placental abnormality and 6cases (11.1%) had shown umbilical abnormality. Congenital anomalies were common between gestational age 35-39weeks and birth weight range 250-1000grams. This study highlights the importance of fetal autopsy in confirming the prenatal diagnosis